Open Box Protocol (OBP) - Paulo Loureiro; Saverio Mascolo; Edmundo Monteiro (Proceedings of the 3rd International Conference on High Performance Computing and Communications, 2007)
In this paper we propose a new explicit congestion control approach, Open Box Protocol (OBP). The OBP gives sources the capacity to look inside the network and to make their congestion control decisions, based, not only on packets loss or packets delay, but also based on another kind of information. For example, the most restricted interface capacity, the available bandwidth, the RTT variations or the presence of heterogeneous transmission means. In the paper we describe the OBP and discuss its evaluation results based on ns-2 simulations. The results show the OBP s capacity to provide traffic sources with the required information, in static or dynamic network scenarios, and to make correct and quick congestion control decisions. Also, it is visible that the OBP avoids the full queue problem and tries to keep the queues near zero occupation.